Improving hard metal implant and soft tissue integration by modulating the “inflammatory-fibrous complex” response - Peina Huang; Jieyun Xu; Lv Xie; Guangqi Gao; Shoucheng Chen; Zhuohong Gong; Xiaomei Lao; Zhengjie Shan; Jiamin Shi; Zhaocai Zhou; Zhuofan Chen; Yang Cao; et al. (Bioactive Materials, 2023)
Soft tissue integration is one major difficulty in the wide applications of metal materials in soft tissue-related areas. The inevitable inflammatory response and subsequent fibrous reaction toward the metal implant is one key response for metal implant-soft tissue integration. It is of great importance to modulate this inflammatory-fibrous response, which is mainly mediated by the multidirectional interaction between fibroblasts and macrophages. In this study, macrophages are induced to generate M1 and M2 macrophage immune microenvironments. Their cytokine profiles have been proven to have potentially multi-regulatory effects on fibroblasts. The multi-reparative effects of soft tissue cells (human gingival fibroblasts) cultured on metal material (titanium alloy disks) in M1 and M2 immune microenvironments are then dissected. Fibroblasts in the M1 immune microenvironment tend to aggravate the inflammatory response in a pro-inflammatory positive feedback loop, while M2 immune microenvironment enhances multiple functions of fibroblasts in soft tissue integration, including soft tissue regeneration, cell adhesion on materials, and contraction to immobilize soft tissue. Enlighted by the close interaction between macrophages and fibroblasts, we propose the concept of an “inflammatory-fibrous complex” to disclose possible methods of precisely and effectively modulating inflammatory and fibrous responses, thus advancing the development of metal soft tissue materials.